2018
DOI: 10.1155/2018/3616942
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Stress Sensitivity and Influence Factors of Shale under Varying Stress

Abstract: Shale reservoirs are characterized by extremely low permeability and high clay content. To further study the stress sensitivity of a shale reservoir, the Lower Cambrian shale in north Guizhou was utilized. Through laboratory testing, the relationships between the shale porosity and permeability and the effective stress were established, and the stress sensitivity of shale was analysed. The mechanical properties and mineral composition of this shale were studied by rock mechanics testing and X-ray diffraction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…During coring and core retrieval, stress unloading and core relaxation can induce a large number of partings, resulting in the formation of micro fractures [24]. Also, as the core is extracted from in-situ conditions, the core expands gradually due to de-compaction or stress relief and other effects over time such as slow gas evolution, leading to inelastic deformation and volumetric expansion sometimes in excess of 6 to 8% [26,27]. This results in an increase of porosity and significant increase in permeability leading to inconsistent results in their measurements.…”
Section: Micro Fracturing Due To Stress Relief/water Intrusionmentioning
confidence: 99%
See 1 more Smart Citation
“…During coring and core retrieval, stress unloading and core relaxation can induce a large number of partings, resulting in the formation of micro fractures [24]. Also, as the core is extracted from in-situ conditions, the core expands gradually due to de-compaction or stress relief and other effects over time such as slow gas evolution, leading to inelastic deformation and volumetric expansion sometimes in excess of 6 to 8% [26,27]. This results in an increase of porosity and significant increase in permeability leading to inconsistent results in their measurements.…”
Section: Micro Fracturing Due To Stress Relief/water Intrusionmentioning
confidence: 99%
“…However, crushing may eliminate micro Darcy (and higher) permeability, especially in texturally complex, siltier, or sandier unconventional reservoirs [24]. Also, care must be taken for shale where organic matter and clay content exceeds 43% as, due to their matrix-supported fabric, they are likely to have lower elastic modulus, higher compressibility, and a greater stress sensitivity coefficient [27]. This renders them prone to plastic shear and contraction and alteration of their pore structure [34].…”
Section: Micro Fracturing Due To Stress Relief/water Intrusionmentioning
confidence: 99%
“…The shale matrix has the characteristics of small pore throats and extremely low permeability. More than 90% of shale gas wells need to undergo shale reservoir fracturing before they can be directly put into production [12][13][14]. The research on shale gas in my country started late.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that under certain high normal stress, the fracture permeability decreased with the increase of contact normal stress. Wu et al 36 conducted a rock mechanics test on Lower Cambrian shale in the northern part of China. It was found that the porosity and permeability of the shale decreased with the increase of effective stress, and the mineral composition of the shale had an important influence on the shale stress sensitivity.…”
Section: Introductionmentioning
confidence: 99%